PENERAPAN PENINGKATAN FASILITAS GREENHOUSE MELALUI PENYEDIAAN STORAGE SHELVES UNTUK TANAMAN MERICA DAN LABEL KEMASAN - Muhammad Aqdar Fitrah; Alfridha Dwi Putri; Hermin Hardyanti Utami; Hermansyah Hermansyah; Syaiful Syaiful (Universitas Mataram, 2026)
This community service aims to improve the efficiency and productivity of pepper cultivation by the Tani Sejahtera Small and Medium Enterprises (SMEs) in Balumbung Village by providing storage shelves in a greenhouse system and product packaging labels. Currently, supporting facilities such as storage shelves are still limited, where pots are arranged on the floor without any arrangement, making mobility and monitoring difficult, and increasing the risk of damage and contamination. Problems with packaging labels include limited understanding of label design, lack of knowledge regarding mandatory information, such as composition and production date. For this reason, the Bantaeng Manufacturing AK lecturer team will provide shelves made of rust-resistant metal and produce packaging labels, as well as become the basis for designing solutions or interventions, such as label design training, licensing assistance, or the provision of appropriate technology. Thus, this research is expected to contribute to improving the quality of MSME packaging. The activities carried out for five months, including needs identification, planning, procurement, installation, socialization, and monitoring and evaluation. This activity is expected to increase space efficiency and can be replicated by other farmer groups as an application of appropriate technology that supports food security. Keywords: Greenhouse, Pepper Plant, Storage Shelves, Packaging Label